PHARMACOECONOMIC JUSTIFICATION OF A WIDER USE OF PREVENTIVE HEMOPHILIA THERAPY IN THE RUSSIAN FEDERATION - M. Yu. Frolov; V. A. Rogov (IRBIS LLC, 2018)
The aim - assess the clinical advantages and economic burden of various treatment strategies in patients with hemophilia A in the Russian Federation and propose the ways of optimizing this area of medical care.Materials and methods. A mathematical model describing the current (2017) approach to therapy of hemophilia A in the RF and two additional treatment scenarios are proposed. A partial switch of patients from the "therapy on demand" to the standard and personalized preventive therapy was also simulated. Based on this mathematical model, the treatment outcomes, the costs of outpatient, hospital and social care were evaluated for the treatment of hemophilia A and its complication; a cost-effectiveness analysis was also performed.Results. Published reports demonstrated a high efficacy of preventive therapy with replacement of coagulation factors VIII in comparison with therapy on demand in the treatment of hemophilia A. Segmentation of the current population of patients with hemophilia A in the RF revealed that the on-demand therapy is the most common approach in adult patients (64%), whereas the standard prophylaxis is used in most children (80%). As calculated, under the current treatment approach, the total number of bleedings is about 58,710 per year, and the number of potentially targeted joints - 3,409 in adults; the figures for children are 3, 817 and 213, respectively. The application of scenario 1 allows for a significant reduction in negative outcomes: i.e. by 62.1% and 62.4% for the risk of bleedings and targeted joints (respectively) in adults if the prevention strategy is increased to 80%; and by 44.2% and 46.2% in children if the prevention is increased to 100%. Simulated scenario 2 allows for achieving even more significant results - a reduction in the number of bleedings and targeted joints by 62.4 and 62.7% in adults and by 47.9 and 50% in children. Transition to simulated scenarios in most cases requires an increase in the overall budget expenses, and also implies a reshuffle of the expenses between different items. For example, increasing the share of prevention therapy leads to increased expenses for the replacement pharmacotherapy in parallel to a reduction in expenses associated with negative outcomes of the disease (endoprosthetics, disability, etc.). In the next 50 years, in terms of the costs, the difference between scenarios 1 and 2, on the one hand, and the current therapy, on the other, is expected to decrease from 26 to 17% and from 26 to 15%, respectively, due to the reduced cost of temporary disability, treatment of bleeding and replacement / re-replacement of joints. According to the "cost-effectiveness" analysis, the best-fit therapy regimen is scenario 2 (personalized prophylaxis), whereas the "current therapy" scenario is the least effective. Based on the ICER analysis, the additional expenses associated with a wider use of preventive therapy in scenarios 1 and 2 do not exceed one GDP per capita, and the technologies are cost-effective.Conclusion. In both clinical and economic aspects, the most effective method of treating severe and moderate haemophilia A is preventive therapy with coagulation factor VIII. Expanding this approach will improve the quality of medical care for patients with hemophilia A.